Mongolia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper analyzes economic development in Mongolia during 1997-99. Economic performance in 1997 was impressive. Aided by strong political support for rapid reform and a generally favorable external environment, financial policies were tightened, and significant reductions in inflation were achieved. Broad-based structural reforms were also undertaken, including steps to restore confidence in the banking system. However, conditions changed abruptly in 1998 as deterioration in the external environment and domestic political problems combined to erode the momentum for reform.